The Influence of Training Programs, Workplace Facilities, and Peer Support on the Performance of Health Workers in Remote Area - Alfred Hartoyo Alphanto; Leni Meipina Ginting; Emanuel Verrell Didy; Gladys Bintang Muliariski (Universitas KH. Abdul Chalim Mojokerto, 2025)
Health workers in the Sangihe Islands, a remote region of North Sulawesi, Indonesia, face challenges due to geographic isolation, limited resources, and inadequate infrastructure, which impact their ability to deliver quality care. This research aims to explore how these three factors (training programs, workplace facilities, and peer support) affect health worker performance in such settings. Using a quantitative survey methods approach, the study gathers primary data from 21 healthcare professionals working in the Polkes 13.09.01 Clinic in Sangihe. SmartPLS 3.2 software was employed for analyzing this research. The findings of this study reveal that training programs and peer support significantly enhance health workers' job performance. However, while workplace facilities are important, they were not found to have a significant impact on health worker performance in this study. The results offer valuable insights for policy development and practical interventions aimed at strengthening health systems in underserved regions. Future studies should involve a larger sample size to provide more comprehensive insights into the factors influencing health worker performance in remote healthcare settings.